Pengaruh Penerapan Gaya Mengajar Komando terhadap Kemampuan Backhand Servis dalam Permainan Bulu Tangkis pada Siswa SMK 2 Tondano - Andreas Fidi Mangundap; Nolfie Piri; J.J Mangindaan (STIKES Columbia Asia Medan, 2024)
Based on preliminary observations made in the field at SMK Negeri 2 Tondano, especially in class XI students, it appears that there is still room for improvement in terms of student mastery of the basic techniques of the backhand serve. This can be seen in badminton games by looking at students' readiness to hit a backhand serve, and how calm they are when serving backhand. After identifying the sources of the problem above, one of the most influential is the use of teaching techniques in the learning process that are less relevant to the sport being taught, in this case badminton. Based on the facts given above, the use of relevant, effective, and efficient teaching techniques is very important to increase student interest in learning and improve the ability to smash backhand serves in badminton games. The research instrument used is a short serve test in badminton games. The findings of this study indicate that there is an influence between the use of command teaching techniques and the improvement of backhand service skills in badminton games of SMKN 2 Tondano students, based on the results of hypothesis testing using t test statistics.